2004
DOI: 10.1016/j.jhsb.2003.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The Crepe Bandage as an Alternative to the Esmarch Bandage for Upper Limb Exsanguination: A Volumetric Comparison Study

Abstract: A study was carried out to compare the effectiveness of upper limb exsanguination using the Esmarch bandage, a crepe bandage and the Rhys-Davies exsanguinator. Upper limb volume changes were measured in ten volunteers using a water displacement method. The crepe bandage produced a mean volume reduction of 59 ml (range, 39-94), which was very similar to the Esmarch bandage, which achieved 63 ml (range, 42-101). This difference is negligible in practical terms. Both bandages were more effective than the Rhys-Dav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The results are in accordance with previous experimental studies (Alshawi and Scott, 2004; Blond and Madsen, 2002), and also with the clinical study of Colville and Small (1986). However, contrary to Colville and Small who found that about 3% of the patients had too little blood in the operative field, we did not observe this problem.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results are in accordance with previous experimental studies (Alshawi and Scott, 2004; Blond and Madsen, 2002), and also with the clinical study of Colville and Small (1986). However, contrary to Colville and Small who found that about 3% of the patients had too little blood in the operative field, we did not observe this problem.…”
Section: Discussionsupporting
confidence: 93%
“…Several different methods of exsanguination are used in hand surgery and no consensus exists as to which is best (Burchell and Stack, 1973; Colville and Small, 1986; Esmarch, 1873; Harris et al, 2002), though experimental studies have found that Esmarch bandaging is the most effective (Alshawi and Scott, 2004; Blond and Madsen, 2003a,b; Fancourt-Smith et al., 1990; Harris et al, 2002). However, Esmarch bandaging is time consuming and has potential side effects, so other methods such as simple elevation or “hand over hand squeezing” (the squeeze method) are widely used.…”
mentioning
confidence: 99%
“…Second, the action of rolling the latex back produces an exsanguination of the finger and therefore bloodless surgery. The concept of exsanguinating a digit or limb is used in other disciplines, for example, by chiropodists when performing partial matricectomies and by hand surgeons in upper limb surgery 2 …”
Section: British‐style Digital Tourniquetmentioning
confidence: 99%
“…Obtaining maximum exsanguination of the hand, preserving sterility, and avoiding trauma to the digits: a simple technique Dear Sir, Exsanguination of the hand and application of a tourniquet is a prerequisite for most hand surgery. Several techniques have been described, including the use of the Rhys-Davies exsanguinator (Rhys-Davies and Stotter, 1985), crepe bandage (Alshawi and Scott, 2004), simple limb elevation, gauze bandage, Esmarch bandage, Pomidor roll-cuff, Urias bag, and squeeze method (Blond and Madsen, 2002). The unsterile Rhys-Davies exsanguinator has been reported to be associated with an increased risk of transmission of infection (Ballal et al, 2007) and to be less effective than an Esmarch or crepe bandage (Alshawi and Scott, 2004).…”
mentioning
confidence: 99%